Respostas
respondido por:
2
= {34 + [ 48 : (3 x 4)] - 19}
= {34 + [ 48 : 12] - 19}
= {34 + 4 - 19}
= {38 - 19}
= 19
= {34 + [ 48 : 12] - 19}
= {34 + 4 - 19}
= {38 - 19}
= 19
respondido por:
1
{34+[48:(18-15)*4]-19} --->
{34+[48:3*4]-19} --->
{34+[48:12]-19} --->
{34+4-19} --->
{38-19} --->
R.: 19
{34+[48:3*4]-19} --->
{34+[48:12]-19} --->
{34+4-19} --->
{38-19} --->
R.: 19
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás